IMPLEMENTASI PROGRAM MADRASAH DINIYAH SEBAGAI UPAYA PENGUATAN PENDIDIKAN KARAKTER - Faqih, Laila (Lembaga Penelitian dan Pengabdian Masyarakat Institut Agama Islam Al-Khairat Pamekasan, 2023)
The purpose of this research is to find out the implementation of the madrasah diniyah and the internalization of character education values. The research methods used was the qualitative descriptive approach. Research result: first, the learning process from start to finish has been well programmed and scheduled through a curriculum set by the principal of the madrasa and carried out by the teaching team. Second, the implementation of learning is carried out effectively and efficiently, there are 2 hours of lessons every day, each subject consist of 45 minutes. Islamic subject namely; fiqh, morality, hadith, tafsir, tajwid, imla', Arabic language, nahwu, shorrof, tarikh and i'lal, the methods used are lectures, discussions and questions and answers. Third, evaluation of teachers and students. Teacher evaluation every month in the fourth week. Evaluation of students in the months of Sha'ban and Maulid, evaluation of written and oral test assessments. Fourth, the madrasah diniyah of Sabilal Muhtadin can strengthen the character education of students. Keyword: Implementation, madrasa diniyah, character education.